BUMDes Peran Badan Usaha Milik Desa (Bumdes) Sepakat Jaya Mandiri Dalam Meningkatkan Kesejahteraan Masyarakat Di Gampong Tingkeum Manyang Kecamatan Kutablang Kabupaten - Rizka, Siti Nura; Rusna, Rusnawati (JAROW: Journal of Ar-Raniry on Social Work, 2024)
Community welfare is a condition that causes people to feel safe, prosperous and safe and free from all kinds of disturbances and difficulties. One way to improve community welfare is through the existence of Village-Owned Enterprises (BUMDes). BUMDes is a business entity whose capital is wholly or largely owned by the village directly through participation in village assets, which are allocated for the management of goods, services and other commercial activities for the welfare of the village community. BUMDeas also aims to increase the village's original income. To find out how BUMDes improve the welfare of the people of Gampong Tingkeum Manyang, Kutablang District, Bireuen Regency, research was conducted with the title "The Role of Village-Owned Enterprises (Bumdes) Sepakat Jaya Mandiri in Improving Community Welfare in Gampong Tingkeum Manyang, Kutablang District, Bireuen Regency". The method used in this research is a descriptive qualitative approach with data collection techniques through observation, interviews and documentation. The results of the research show that the implementation of BUMDes' agreed Jaya Mandiri business has been carried out well. BUMDes Sepakat Jaya Mandiri has built business units such as a trading business unit that opens a Pertamina shop business, an agricultural business unit that provides pumping, and a village-owned shop rental business unit. With the existence of these three business units, BUMDeas has opened up employment opportunities and business places for the community in Tingkeum Manyang village so that it can improve community welfare.